Commercial baking with entrepreneurship - Dinaga, Maria Rhoda D.; Lirazan, Tenie P. (Intramuros, Manila : Mindshapers Co., Inc., 2022)
The unit of competency "Commercial Baking with Entrepreneurship" contains knowledge, skills and attitudes required for bread and pastry production NC II.
CHAPTER 1. Introduction to baking -- 2. Sanitation and safety -- 3. Baking Terminologies -- 4. Baking tools and equipment -- 5. Baking Ingredients -- 6. Baking Math -- 7. Baking Principles -- 8. Classification of bakery products -- 9. Steps of Breadmaking -- 10. Quick Breads -- 11. Cakes and Icing -- 12. Cookies -- 13. Pies and Tarts -- 14. Syrups, Creams, Custards and Chocolate.
Includes bibliographical references.
Keywords: BREAD; PASTRY